2022
DOI: 10.1152/jn.00347.2021
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity in bone-conducted amplitude-modulated cervical vestibular-evoked myogenic potentials: harmonic distortion products

Abstract: Otolith organs of the balance system, the saccule and utricle, encode linear acceleration. Integrity of the saccule is commonly assessed using cervical vestibular evoked myogenic potentials (cVEMPs) arising from an inhibitory reflex along the vestibulospinal pathway. Conventional approaches to eliciting these responses use brief, transient sounds to elicit onset responses. Here we used long-duration amplitude-modulated (AM) tones to elicit cVEMPs (AMcVEMPs) and analyzed their spectral content for evidence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In auditory steady-state responses elicited by AM tones, similar distortion products are found at both the modulation frequency and its second harmonic due to the half-wave rectification of cochlear hair cells (Cohen et al 1991; Lins et al 1995; Bidelman & Bhagat 2020). A detailed analysis of harmonic distortion products from the present study are reported separately in Clinard et al(2022). While the auditory system’s nonlinear properties and subsequent functional implications are well-understood, it is currently unknown how nonlinearity of otolith hair cells relates to functional balance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In auditory steady-state responses elicited by AM tones, similar distortion products are found at both the modulation frequency and its second harmonic due to the half-wave rectification of cochlear hair cells (Cohen et al 1991; Lins et al 1995; Bidelman & Bhagat 2020). A detailed analysis of harmonic distortion products from the present study are reported separately in Clinard et al(2022). While the auditory system’s nonlinear properties and subsequent functional implications are well-understood, it is currently unknown how nonlinearity of otolith hair cells relates to functional balance outcomes.…”
Section: Discussionmentioning
confidence: 99%